И.ЮСУПОВ ЛИРИКАСЫНДА МУЗЫКАҒА БАЙЛАНЫСЛЫ СИМВОЛЛАР - Даниярова, Г.П. (SCIENCE and SOCIETY, 2022)
The article provides a poetic analysis of the symbols associated with music used in the lyrics of the national poet, Hero of Uzbekistan I. Yusupov. The connection is determined between artistic words and music by the example of lyrical poems. The article contains ideas about the use of the words muse, lyre in the works of I. Yusupov as a symbol, as well as the mythological hero Orpheus.
Keywords: music; lira; muse; Orpheus; myth; symbol